(untitled) (Revista da EGN, 2023)
The study to be presented is about observing the war and crisis games research domain regarding the Chinese BRI (Belt and Road Initiative). In this respect, it will be necessary to detect the trends and uses of wargaming as a tool to train and predict, considering the state of the art of discipline. Given the transitions and developments of Chinese projection in the international system, it is intended to qualify how the arrangements under development collaborate with the project to expand the influence of the Belt and Road Initiative. Likewise, there is the need to segment the principles and models in progress for a possible exploratory typification derived from the study. For this purpose, we use primary and secondary sources related to the government structure and the intelligentsia system, primarily from think tanks and universities. As such, the understanding is that observing the characteristics in progress can allow for estimating the synergies or gaps between the model of influence and expansion in progress and the domain of wargaming developments. Then, we highlight that the wargaming knowledge is part of building upon the national security agenda to uphold Chinese international participation from the constitution of the Chinese national identity. Furthermore, we identify ways wargaming could help with the challenges and opportunities in the literature on BRI. We note that alongside the wargaming national security perspective, the technical training apparatus marks an influential trend for Chinese defense development by the West.